The dynamics of memory consolidation of landmarks. Issue 4 (16th January 2017) - van Ekert, Janneke; Wegman, Joost; Jansen, Clemens; Takashima, Atsuko; Janzen, Gabriele
ABSTRACT: Navigating through space is fundamental to human nature and requires the ability to retrieve relevant information from the remote past. With the passage of time, some memories become generic, capturing only a sense of familiarity. Yet, others maintain precision, even when acquired decades ago. Understanding the dynamics of memory consolidation is a major challenge to neuroscientists. Using functional magnetic resonance imaging, we systematically examined the effects of time and spatial context on the neural representation of landmark recognition memory. An equal number of male and female subjects (males N  = 10, total N  = 20) watched a route through a large‐scale virtual environment. Landmarks occurred at navigationally relevant and irrelevant locations along the route. Recognition memory for landmarks was tested directly following encoding, 24 h later and 30 days later. Surprisingly, changes over time in the neural representation of navigationally relevant landmarks differed between males and females. In males, relevant landmarks selectively engaged the parahippocampal gyrus (PHG) regardless of the age of the memory. In females, the response to relevant landmarks gradually diminished with time in the PHG but strengthened progressively in the inferior frontal gyrus (IFG). Based on what is known about the functioning of the PHG and IFG, the findings of this study suggest that males maintain access to the initially formed spatial representation of landmarks whereas females become strongly dependent on a verbal representation of landmarks with time. Our findings yield a clear objective for future studies. © 2017 Wiley Periodicals, Inc.